THINKING LIKE A MONKEY. - Adler, Jerry (Smithsonian, 2008)
The article profiles Laurie Santos, a primate researcher and psychologist at Yale University. Santos has traveled yearly to the private island of Cayo Santiago, which is off the coast of Puerto Rico, since 1993 to study rhesus macaques in an effort to determine how and if the monkeys think, examine their level of knowledge, and determine if they have theory of mind; the ability to impute thoughts and intentions to another individual. Details of Santos work with the monkeys and several human volunteers are presented.